Women as Breadwinners in Maureen Sherry’s Opening Belle - Margaretha Finna Calista; Wening Udasmoro (Journal of Language and Literature, 2021)
There have been many popular fiction novels in the literature world that raise how women enter the economic aspect. One of them is the novel Opening Belle written by Maureen Sherry and published in 2016. Opening Belle represents women’s participation in the financial sector because they want a good life. This research is studied with the feminist political economy theory proposed by Jacqui True. In her book, The Political Economy of Violence against Women, True explains that economic globalization has changed women’s lives becoming financially independent. However, on the other hand, women involved in the public sphere are underappreciated and receive sexual harassment or violence, making it difficult for women to participate in the economic aspect. This research uses the descriptive qualitative method. With this method, the writer takes parts of the novel in the form of words, sentences, paragraphs which explain the economic aspect and women’s participation in it. This research is analyzed through the explanations and utterances of the characters. The results of this study are: first, the participation of women as breadwinners in this novel is started as part of her life experiences and is driven by the hardships of her family; second, women are highly motivated figures so that they implement several strategies to survive in their office, namely by proving their competence, joining the GCC women’s community and voicing equal rights in the workplace. In conclusions, economic globalization opens up women’s opportunity to become the sole breadwinner in the family.